Cervical Cancer with Bulky Tumor: A Case Report - Hezron, Teuku Maizaldi; Hasanuddin, Hasanuddin (CoinReads Media Prima, 2025)
Introduction: Cervical cancer is a malignancy originating from the cervix and represents one of the most common cancers affecting women both globally and in Indonesia. Meanwhile, bulky tumor is defined as a lesion measuring ≥4 cm in diameter. Neoadjuvant chemotherapy followed by radical surgery (NACT-RS) has emerged as a viable treatment option for stages IB3 and IIA2 cervical cancer, especially in settings where radiotherapy resources are limited or unavailable. Case Report: A 28-year-old female was presented with abnormal vaginal bleeding persisting for four months. The bleeding was bright red and foul-smelling. The patient also reported postcoital bleeding beginning seven months prior to presentation. A cervical biopsy was performed, and histopathological analysis confirmed a diagnosis of non-keratinizing squamous cell carcinoma. Due to the large tumor size, the patient underwent three cycles of chemotherapy prior to radical hysterectomy as part of her treatment plan. Conclusion: In patients with bulky cervical tumors, neoadjuvant chemotherapy followed by radical hysterectomy can offer favorable perioperative outcomes and remains a critical treatment approach.